Rowers with a recent history of low back pain engage different regions of the lumbar erector spinae during rowing. Issue 11 (November 2019) - Martinez-Valdes, Eduardo; Wilson, Fiona; Fleming, Neil; McDonnell, Sarah-Jane; Horgan, Alex; Falla, Deborah
Abstract: Objectives: Despite the high prevalence of low back pain (LBP) in rowers, there are few studies investigating changes in lumbar muscle activation in rowers with a recent history of LBP. Such knowledge is relevant to understand potential mechanisms contributing to the maintenance and recurrence of LBP in rowers. For the first time, we evaluate the spatial distribution of erector spinae (ES) activity in rowers with and without a recent history of LBP, using a novel application of high-density surface electromyography (HDEMG). Design: Cross-sectional study. Methods: Asymptomatic rowers ( N  = 10) and rowers with a recent history of LBP ( N  = 8) performed 7 × 4-min exercise bouts (rowing ergometer) until volitional exhaustion. HDEMG signals were acquired bilaterally over the lumbar ES and the root mean square (RMS) amplitude and entropy were analyzed. In addition, the y -axis coordinate of the barycentre (RMS-map) was used to assess changes in ES spatial activation. Results: As the load increased, rowers with LBP showed higher amplitude ( p  < 0.01) and less complexity (entropy) of the HDEMG signals ( p  < 0.001). In addition, rowers with LBP showed opposite displacements of the barycentre, specifically showing a caudal shift of muscle activity at high intensities ( p  < 0.001). Conclusions: Both the magnitude of activation and distribution of ES activity were altered in rowers with a recent history of LBP. The lower complexity of signals together with the caudal displacements of the barycentre suggest an inefficient recruitment of the ES as the load progressed. Modification of the rowing technique in conjunction with feedback from HDEMG might prove useful in future studies.